Community Assistance in the Creation of Biopores as an Effort to Prevent Flooding in RW 01 Karyamulya Village - Cahya, Cindy Alidya; Kusnawan, Aep (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2024)
One of the environmental problems that currently occurs frequently is the problem of flooding which is caused by high rainfall and the absence of water absorption resulting in flooding. And based on observations of the surrounding environment, what is becoming an issue is the processing of waste consisting of organic and inorganic materials that are still left untreated. Therefore, it is necessary to provide assistance in making biopores to prevent flooding. This service uses the Participatory Action Research (PAR) method, a service method that involves direct community participation. This method aims to encourage transformative action and liberate society from the shackles of ideology and power relations. This service begins with an approach to residents to build relationships with each other so that they get information regarding existing problems. Next, initial mapping is carried out which aims to determine the population, number of schools, environmental and economic conditions and potential that can be identified so as to get to the problem in depth and produce work from the results of research carried out during the KKN implementation. Then programming was carried out in RW 01, Karyamulya Village, Batujaya District, Karawang Regency and the Sasaram of this service were residents of RW 01. The final stage was to close and evaluate the work program that had been implemented. This assistance activity in making biopores can increase public knowledge about biopore holes, increase water absorption capacity, and reduce the problem of organic waste. Residents who take part in this activity can understand and learn about the tools and procedures for making and maintaining biopores.